Pedestrian day experience in Thimphu, Bhutan - Ahmed, Ishtiaque (2013)
Thimphu, the capital city of Bhutan faces significant traffic congestion and air pollution as traffic continues to grow rapidly. In June 2012, the Government designated every Tuesday as a vehicle free day in the core Thimphu area, known as the Pedestrian Day (PD). A considerable number of people resisted the initiative with dissatisfaction. The Government then announced in November 2012 that the PD would be observed on the first Sundays of each month. Ultimately the entire initiative had to be withdrawn in August 2013. Results of a survey conducted by the Center for Research Initiatives (CRI) after the PD initiative was just initiated were compared with the results of a new survey conducted once the PD initiative was withdrawn. While the first stage survey showed that 57.8% of respondents supported the concept and 54.0% wanted discontinuation of the PD, the study found that at the second stage, more respondents, i.e. 62.0%, supported the idea but also more respondents (63.3%) did not want the PD to be continued. Primary factors identified were; a) lack of stakeholder consultation; b) inadequate implementation planning; and c) inadequate facilitation of alternatives. The experience of Pedestrian Day in Thimphu suggests that prior stakeholder consultations and preparatory measures are necessary for the successful implementation of this type of sustainable transportation program.